Development and evaluation of microsatellite markers for Acer miyabei (Sapindaceae), a threatened maple species in East Asia1. (5th June 2015) - Saeki, Ikuyo; Hirao, Akira S.; Kenta, Tanaka
Abstract : Premise of the study: Twelve microsatellite markers were developed and characterized in a threatened maple species, Acer miyabei (Sapindaceae), for use in population genetic analyses. Methods and Results: Using Ion Personal Genome Machine (PGM) sequencing, we developed microsatellite markers with perfect di‐ and trinucleotide repeats. These markers were tested on a total of 44 individuals from two natural populations of A. miyabei subsp. miyabei f. miyabei in Hokkaido Island, Japan. The number of alleles per locus ranged from two to eight. The observed and expected heterozygosities per locus ranged from 0.05 to 0.75 and from 0.05 to 0.79, respectively. Some of the markers were successfully transferred to the closely related species A. campestre, A. platanoides, and A. pictum . Conclusions: The developed markers will be useful in characterizing the genetic structure and diversity of A. miyabei and will help to understand its spatial genetic variation, levels of inbreeding, and patterns of gene flow, thereby providing a basis for conservation.